In pregnancy increased maternal STAI trait stress score shows decreased insulin sensitivity and increased stress hormones. (October 2017) - Valsamakis, Georgios; Papatheodorou, Dimitrios C.; Chalarakis, Nikolaos; Vrachnis, Nikolaos; Sidiropoulou, Elpida J.; Manolikaki, Maria; Mantzou, Aimilia; Margeli, Alexandra; Papassotiriou, Ioannis; Chrousos, George P.; Mastorakos, George
Highlights: Women with higher STAI trait scores (≥40) had greater serum cortisol and CRH concentrations. Women with higher STAI trait scores (≥40) had lower insulin sensitivity index values (ISI). CRH concentrations correlated positively with maternal STAI state score, HOMAR (insulin resistance), 1 st and 2 nd phase insulin secretion and negatively with ISI. STAI state score correlated positively with HOMAR. Abstract: Introduction: Chronic or acute stressors influence maternal and fetal Hypothalamus-Pituitary-Adrenal Axes (HPA) during pregnancy. In this study, the effect of maternal stress into maternal insulin sensitivity was investigated during pregnancy. Materials and methods: Eighty-two pregnant women [aged 27.1 ± 2.5 (mean ± SD) yrs; BMI = 25 ± 2.2 kg/m 2 ] had at the 2 nd and 3 rd trimesters anthropometry, fasting blood samples (cortisol, Corticotropin Releasing Hormone (CRH), active amylin, Interleukin (IL6)), Oral Glucose Tolerance Test (OGTT) for glucose and insulin, state-trait anxiety inventory (STAI) trait and state questionnaires (for stress assessment). Results: Maternal cortisol, CRH and STAI state score increased significantly from 2 nd to 3 rd trimester. At these trimesters women with STAI trait scores ≥40 had greater serum cortisol and CRH concentrations and lower insulin sensitivity index (ISI) values than those with scores <40 while STAI trait score predicted negatively ISI. At the 2 nd trimester maternal CRH concentrations correlated positively with maternal STAI state, Homeostatic Model Assessment Insulin Resistance (HOMAR), 1 st and 2 nd phase insulin secretion and negatively with ISI. STAI trait correlated negatively with ISI. STAI state correlated positively with maternal systolic blood pressure and HOMAR. At the 3 rd trimester STAI trait correlated negatively and positively with ISI and STAI state, respectively, while STAI state correlated positively with HOMAR. In women with STAI state scores ≥40, these scores correlated positively with maternal CRH. Conclusions: In normal pregnant women, enhanced long-term stress is associated with decreased insulin sensitivity. Both long- and short- term stress are associated with enhanced maternal HPA axis and increased placental CRH secretion.